Encyclopaedia of elementary education; Vol II Philosophical and sociological perspectives on education - Agarwal, J. C. (ed); Agarwal, J. C. (ed) (Delhi Anshah publishing house, 2012)
PHILOSOPHICAL PERSPECTIVES ON EDUCATION